Preventable Severe Thalassemia among Children - Chaiwat Rerkswattavorn (2019)
© 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group. This retrospective study analyzed 27 children with preventable severe thalassemia born to 24 at-risk couples between 1997 and 2017. The couples were categorized into two groups: the prenatal diagnosis (PND) group (n = 8) and the non PND group (n = 16). In the PND group, following comprehensive counseling on having a fetus with thalassemia, six couples decided to continue the pregnancy (n = 6). Termination of the two remaining fetuses was excluded as the thalassemia status was reported at a gestational age of 24 weeks. In the non PND group, medical errors were found in the misdiagnosis of couples as non thalassemia carriers (n = 4) and not offering PND to couples with known thalassemia carrier status when attending the antenatal clinic (ANC) (n = 2). Additionally, parental ignorance was found in parents experiencing their own thalassemia, or that of their spouse or child (n = 6). The remaining couples (n = 4) with known carrier status either directly refused PND or were ineligible for it. A total of five divorces (5/24 = 20.8%) occurred in the PND (n = 2) and the non PND (n = 3) groups. Knowledge, beliefs, religion, experience of thalassemia, as well as the sex of the at-risk fetus all influenced parental decisions. Therefore, both medical personnel and parents are key in preventing new cases of thalassemia. Parents should be aware of the consequences of having children with severe thalassemia, while medical personnel should provide accurate carrier detection and PND.